A study on starch profile of rajma bean (Phaseolus vulgaris) incorporated noodle dough and its functional characteristics. (1st August 2015) - Bharath Kumar, S.; Prabhasankar, P.
Highlights: In vitro starch availability of rajma incorporated noodles reduced by 20%. Overall sensory quality was acceptable even at 30% rajma . Starch profile analysis indicated reduction in RDS and increase in SDS content. HPSEC indicated increased amylopectin content, may be due to SBE isoforms. Abstract: Starch profile reflects functional characteristics like digestibility and product quality. A study was aimed to incorporate rajma in noodle processing to improve product and nutritional quality and also to reduce starch digestibility. It is known that some of the pulses like Kidney beans have an isoforms of Starch-Branching-Enzyme (SBE) helps in converting amylose to amylopectin. Rajma flour was incorporated at 10%, 20% and 30% with T riticum durum and subjected to rheological, physico-chemical and amylose/amylopectin determination using High-Performance-Size-Exclusion-Chromatography (HPSEC). Results revealed that rajma flour decreased peak-viscosity from 954 to 683 BU and increased water absorption. Protein and dietary fiber content increased significantly. Sensory profile showed higher overall quality (>8.5). In vitro starch digestibility reduced from 65% to 49%. Starch profile from HPSEC showed changes in amylose:amylopectin peak, this may be because of the presence of SBE, further studies may be required to support the hypothesis.